Violent Conflict and Breastfeeding: The Case of Iraq - Vidya Diwakar; Michael Malcolm; George S Naufal (Institute of Labor Economics (IZA), 2017)
This study explores the relationship between armed conflict and breastfeeding practices of Iraqi mothers. Using a unique pairing of the Iraq Body Count database, in conjunction with the 2006 and 2011 Multiple Indicator Cluster Surveys for Iraq, we find that increases in conflict-related casualties are associated with a decline in breastfeeding incidence, with some mixed results on breastfeeding duration. We also explore a number of potential causal channels, including interactions with household wealth and accessibility of formula. The results are informative in the context of designing policy aimed at stabilizing the long-term health and productivity of populations in conflict areas.
Keywords: D74; I1; J13; J18; 330; conflict; breastfeeding; Middle East; Iraq